2021
DOI: 10.3389/fimmu.2021.798553
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Applications and Action Mechanisms of Phytochemicals as Alternatives to Antibiotics in Pig Production

Abstract: Antibiotics are widely used for infectious diseases and feed additives for animal health and growth. Antibiotic resistant caused by overuse of antibiotics poses a global health threat. It is urgent to choose safe and environment-friendly alternatives to antibiotics to promote the ecological sustainable development of the pig industry. Phytochemicals are characterized by little residue, no resistance, and minimal side effects and have been reported to improve animal health and growth performance in pigs, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 188 publications
(218 reference statements)
0
21
0
Order By: Relevance
“…Ren’s oligopeptide-1 has the merits of less residue, little drug resistance, fewer side effects, and lower cost. It can improve the animal health and growth performance of pigs and is expected to become a promising feed additive [ 37 ]. It is imperative to develop natural antiviral compounds that can provide new ideas for the treatment and prevention of viral diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Ren’s oligopeptide-1 has the merits of less residue, little drug resistance, fewer side effects, and lower cost. It can improve the animal health and growth performance of pigs and is expected to become a promising feed additive [ 37 ]. It is imperative to develop natural antiviral compounds that can provide new ideas for the treatment and prevention of viral diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemicals have been used for many years to treat various ailments (Li et al, 2021 ), which possess many unique advantages compared with the above several antibiotic alternatives, such as exceptionally rich sources, diverse chemical structures, and multiple biological functions (Porras et al, 2021 ). Therefore, phytochemicals are gaining significant attention as substitutes for antibiotics.…”
Section: Phytochemicalsmentioning
confidence: 99%
“…Due to their excellent properties as antibiotic alternatives, various phytochemicals have been used in animal production as feed additive to improve animal health and growth performance (Li et al, 2021 ; Ayalew et al, 2022 ), and some have been successfully commercialized. In this topic, Yin et al demonstrated that dietary Lycium barbarum polysaccharides (LBPs) supplementation could improve growth performance, antioxidant capacity and immunity, and reduced diarrhea incidence in weaned piglets.…”
Section: Phytochemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, various alternatives were sought to reduce the use of antibiotics in animal production, in order to maintain their health and performance. The types of additives available to increase animal productivity while maintaining the health of the human population include probiotics and prebiotics, plant extracts, essential oils, dietary fiber and enzymes, antimicrobial peptides, functional amino acids, hyperimmune antibodies from eggs, clays, and/or metals [2,3,[7][8][9][10]. The optimal combinations of different compounds, together with good management and breeding practices, can be the key to intensifying the performance and productivity of animals with the aim of reducing and/or replacing antibiotics in the animal industry [3].…”
Section: Introductionmentioning
confidence: 99%